The Diet-Free Revolution : 10 Steps to Free Yourself from the Diet Cycle with Mindful Eating and Radical Self-Acceptance - Conason, Alexis (Berkeley, California : North Atlantic Books, 2021)
" A guide for leaving diet culture and healing your relationship with food"
Includes bibliographical references and index.
Keywords: Self-acceptance; Food habits -- Psychological aspects; Food habits -- Psychological aspects; Diet -- Psychological aspects